2015
DOI: 10.1016/j.bone.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Serine dipeptide lipids of Porphyromonas gingivalis inhibit osteoblast differentiation: Relationship to Toll-like receptor 2

Abstract: Porphyromonas gingivalis is a periodontal pathogen strongly associated with loss of attachment and supporting bone for teeth. We have previously shown that the total lipid extract of P. gingivalis inhibits osteoblast differentiation through engagement of Toll-like receptor 2 (TLR2) and that serine dipeptide lipids of P. gingivalis engage both mouse and human TLR2. The purpose of the present investigation was to determine whether these serine lipids inhibit osteoblast differentiation in vitro and in vivo and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…Flavolipin,a na mino acid-containing lipid (Scheme 10) from Flavobacterium meningosepticum, an opportunistic pathogen that causes pneumonia, meningitis, and septicemia in immune-compromised individuals, such as newborn infants and patients with advanced HIV.A lso called, Lipid 654 due to its mass, Flavolipin has been demonstrated to play ar ole in the development of two chronic inflammatoryd iseases, including [32][33][34] periodontal disease and atherosclerosis and significantly inhibited osteoblast gene expression. [35] Mostr ecently, studies have shown that Flavolipin may be implicated in the development of multiple sclerosis. [36] The lipid chain moiety 17 consists in an omega methylated tetradecanoid acid esterified with an omega methylated 3(R)hydroxy-hexadecanoica cid (Scheme 10).…”
Section: Some Branched Acylated Hfas In Bacterial Lipodipeptidesmentioning
confidence: 99%
“…Flavolipin,a na mino acid-containing lipid (Scheme 10) from Flavobacterium meningosepticum, an opportunistic pathogen that causes pneumonia, meningitis, and septicemia in immune-compromised individuals, such as newborn infants and patients with advanced HIV.A lso called, Lipid 654 due to its mass, Flavolipin has been demonstrated to play ar ole in the development of two chronic inflammatoryd iseases, including [32][33][34] periodontal disease and atherosclerosis and significantly inhibited osteoblast gene expression. [35] Mostr ecently, studies have shown that Flavolipin may be implicated in the development of multiple sclerosis. [36] The lipid chain moiety 17 consists in an omega methylated tetradecanoid acid esterified with an omega methylated 3(R)hydroxy-hexadecanoica cid (Scheme 10).…”
Section: Some Branched Acylated Hfas In Bacterial Lipodipeptidesmentioning
confidence: 99%
“…While LPS produced by P. gingivalis can promote osteoclastogenesis through binding to TLR4 [26], recent studies revealed that serine dipeptide lipids produced by P. gingivalis can act on TLR2 which, in turn, inhibits osteoblastogenesis [27,28]. On the other hand, lipid A derived from P. gingivalis is contaminated with phosphorylated dihydroceramide lipids which can also stimulate TLR2 [29].…”
Section: Introductionmentioning
confidence: 99%
“…These agonists are also produced by common oral and intestinal Bacteroidetes , and they are recovered in chronically inflamed human tissues including destructive periodontal disease and atherosclerosis tissues . The most commonly observed serine dipeptide mono‐fatty acid species is composed of 3‐OH iso‐C 17:0 fatty acid moiety may form a 3‐OH ester linkage to a saturated fatty acid, most frequently to iso‐C 15:0 (see 1 ) . Members of the Bacteroidetes phylum comprise a group of commensal organisms recovered in the human oral and intestinal microbiomes.…”
Section: Introductionmentioning
confidence: 99%
“…2 The most commonly observed serine dipeptide mono-fatty acid species is composed of 3-OH iso-C 17:0 fatty acid moiety may form a 3-OH ester linkage to a saturated fatty acid, most frequently to iso-C 15:0 (see 1). 4 Members of the Bacteroidetes phylum comprise a group of commensal organisms recovered in the human oral and intestinal microbiomes. Oral and intestinal Bacteroidetes organisms have recently been shown to produce novel serine dipeptide lipids identical to those described for specific Flavobacteria.…”
Section: Introductionmentioning
confidence: 99%